ANALISIS LUAS LAHAN PERTANIAN TERHADAP PRODUKSI PADI DI KALIMANTAN UTARA - Rika Harini; Rina Dwi Ariani; Supriyati Supriyati; M Chrisna Satriagasa (Jurnal Kawistara, 2019)
The increasing population in North Kalimantan will affect the provision of land. Agricultural land conversion cannot be avoided to meet the social and economic needs of the population. To find out land conversion and its impacts in North Kalimantan, a study of a) changes in agricultural land area, b) changes in rice production and c) the effect of changes in agricultural land area on North Kalimantan rice production. Quantitative methods of secondary data analysis were carried out to assess rice production and changes in agricultural land presented in frequency tables, graphs and maps. Analysis of the effect of agricultural land area on rice production in North Kalimantan Province was carried out using linear regression analysis. The results showed that the agricultural land area in North Kalimantan in 2012-2017 had a change of 4,955 ha or around 19.56 percent.. Rice commodities in North Kalimantan in general decreased by 25,468 tons or 0.04 percent. While for agricultural land area significantly (0.029) has an effect on rice production in North Kalimantan.